Reconceptualizing Social Media in Arabic Language Learning: Students’ Experiences and Digital Learning Practices - Mustolikh Khabibul Umam; Daluti Delimanugari; Ana Dwi Wahyuni; Zetty Arifah; Rifka Khoirun Nada (Attractive : Innovative Education Journal, 2025)
This study aims to explore students' experiences in using social media for Arabic language learning, analyze the benefits and challenges they experience, and identify strategies that can improve the effectiveness of Arabic language learning through social media. The study used a qualitative approach with a descriptive design. Data were collected through semi-structured interviews with 15 participants who have experience using social media in Arabic language learning. Data were analyzed thematically through the processes of transcription, coding, categorization, theme development, interpretation, and drawing conclusions. The research findings indicate that social media is used to acquire vocabulary, improve listening skills, understand conversations, observe language use in real contexts, search for additional materials, and interact with Arabic learners and speakers. These benefits primarily relate to flexibility, input diversity, access to authentic materials, and opportunities for independent learning. On the other hand, learners face issues of content credibility, distraction, irregular learning, limited direct correction, and difficulty in identifying appropriate sources. This research contributes by positioning social media not merely as a learning medium, but as a social-digital space where learners obtain input, interact, produce language, and develop learning strategies. The research findings indicate that the effectiveness of social media in Arabic language learning is not primarily determined by the platform used, but by the quality of the source, learning objectives, interaction patterns, digital literacy skills, self-regulation, and educator involvement